2008
DOI: 10.1073/pnas.0802866105
|View full text |Cite|
|
Sign up to set email alerts
|

Next generation of adeno-associated virus 2 vectors: Point mutations in tyrosines lead to high-efficiency transduction at lower doses

Abstract: Recombinant adeno-associated virus 2 (AAV2) vectors are in use in several Phase I/II clinical trials, but relatively large vector doses are needed to achieve therapeutic benefits. Large vector doses also trigger an immune response as a significant fraction of the vectors fails to traffic efficiently to the nucleus and is targeted for degradation by the host cell proteasome machinery. We have reported that epidermal growth factor receptor protein tyrosine kinase (EGFR-PTK) signaling negatively affects transduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
527
3
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 504 publications
(544 citation statements)
references
References 53 publications
13
527
3
1
Order By: Relevance
“…The second-generation optimized CsCl purification method described and characterized herein enables flexible purification of vectors of varying serotypes, and importantly results in consistently high vector purity and potency, and comparable in these attributes to vectors prepared for clinical studies. The use of such improved AAV purification methods for pre-clinical studies, combined with further improvements in expression cassettes, use of self-complementary AAV constructs, 23 more efficient serotypes, 8,24 and improved delivery techniques are important strategies to meet the need for high levels of therapeutic transgene expression and support successful translational research.…”
Section: Discussionmentioning
confidence: 99%
“…The second-generation optimized CsCl purification method described and characterized herein enables flexible purification of vectors of varying serotypes, and importantly results in consistently high vector purity and potency, and comparable in these attributes to vectors prepared for clinical studies. The use of such improved AAV purification methods for pre-clinical studies, combined with further improvements in expression cassettes, use of self-complementary AAV constructs, 23 more efficient serotypes, 8,24 and improved delivery techniques are important strategies to meet the need for high levels of therapeutic transgene expression and support successful translational research.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, in stage one, two PCR extension reactions were performed in separate tubes for each mutant. One tube contained the forward PCR primer and the other contained the reverse primer (Zhong et al, 2008b). In stage two, the two reactions were mixed and a standard PCR mutagenesis assay was carried out as per the manufacturer's instructions.…”
Section: Recombinant Aav2 Vectors Plasmids Antibodies and Chemicalsmentioning
confidence: 99%
“…In stage two, the two reactions were mixed and a standard PCR mutagenesis assay was carried out as per the manufacturer's instructions. PCR primers were designed to introduce changes from tyrosine to phenylalanine residues, as well as a silent change to create a new restriction endonuclease site for screening purposes (Zhong et al, 2008b). All multiple mutant AAV2 capsid plasmids were constructed using standard subcloning strategies.…”
Section: Recombinant Aav2 Vectors Plasmids Antibodies and Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that inhibition of the EGFR-PTK mediated phosphorylation of AAV capsid proteins at tyrosine residues results in decreased ubiquitination of AAV capsids and their proteasome-mediated degradation, thereby enabling nuclear transport of AAV vectors and improved gene delivery to the cell nucleus [38] . Based on these results, Zhong et al [39] hypothesized that substitution of surface-exposed tyrosine residues on AAV capsids may lead to the design of AAV vectors that facilitate efficient delivery of genes to the nucleus of target cells at lower doses. Consistent with this hypothesis, they observed that site-directed mutagenesis of surface-exposed tyrosine residues significantly improve the transduction efficiency of AAV vectors (about 10-fold increase) in human epithelial cells in vitro.…”
Section: Molecular Engineering Of Viral Vectorsmentioning
confidence: 99%